The Description in the Poetry of Bashir ibn Burd: A Study of Artistic Techniques, Humanistic Meanings, and Creative Energies (Mesopotamian Journal of Arabic Language Studies, 2021)
After studying the descriptive discourse of Bashar ibn Burd and examining his poetry, we have reached several conclusions. Firstly, the art of description in Burd’s poetry showcases the poet’s ability to use colors and imagery to convey meaning, capturing the reader’s attention and imagination. Secondly, Burd’s style represents a transition and transformation, blending classical poetry with modern sensibilities and language. Thirdly, Burd drew inspiration from nature, often describing the beauty and harshness of the desert, as well as depicting scenes of urban luxury and leisure. Finally, Burd’s poetry employs a dual style, with one more personal and sincere and the other aimed at pleasing the ruling class